2011
DOI: 10.1128/aac.00315-11
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Ceftaroline and Epidemiologic Trends in Staphylococcus aureus Isolates Collected from 43 Medical Centers in the United States in 2009

Abstract: A Staphylococcus aureus surveillance program was initiated in the United States to examine the in vitro activity of ceftaroline and epidemiologic trends. Susceptibility testing by Clinical and Laboratory Standards Institute broth microdilution was performed on 4,210 clinically significant isolates collected in 2009 from 43 medical centers. All isolates were screened for mecA by PCR and evaluated by pulsed-field gel electrophoresis. Methicillin-resistant S. aureus (MRSA) were analyzed for Panton-Valentine leuko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 21 publications
1
58
0
Order By: Relevance
“…A recent report on MRSA strain types from 43 U.S. medical centers by Richter et al (38) shows a larger proportion of USA100 than USA300 isolates among blood isolates nationwide, even though, overall, there were over 3 times as many USA300 isolates recovered across all specimen types compared to USA100 isolates (1,137 versus 377, respectively). Given that five of nine U.S. census regions showed similar data in our convenience sample (where USA100 predominates), we do not believe that our data are necessarily in conflict with those reported by Richter et al (38). Unfortunately, the data in the latter study were not reported by geographic region.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report on MRSA strain types from 43 U.S. medical centers by Richter et al (38) shows a larger proportion of USA100 than USA300 isolates among blood isolates nationwide, even though, overall, there were over 3 times as many USA300 isolates recovered across all specimen types compared to USA100 isolates (1,137 versus 377, respectively). Given that five of nine U.S. census regions showed similar data in our convenience sample (where USA100 predominates), we do not believe that our data are necessarily in conflict with those reported by Richter et al (38). Unfortunately, the data in the latter study were not reported by geographic region.…”
Section: Discussionmentioning
confidence: 99%
“…However, these MRSA failed to become established in hospitals in the UK and Denmark [20]. isolates are increasingly recognised as a cause of hospital-associated bacteraemia [35][36][37]. Indeed, the USA300 epidemic peaked in 2004 leading to the mathematical Page 13 of 34 A c c e p t e d M a n u s c r i p t 13 predictions that the USA300 CA-MRSA strains will eventually displace the HA-MRSA strains owing to the survival advantage of the former as a result of smaller and fewer genes leading to enhanced fitness [38].…”
Section: Hospital-associated Meticillin-resistantmentioning
confidence: 99%
“…The mecA PCRpositive isolates (53.4% of collection) had been analyzed by SCCmec typing and Panton-Valentine leukocidin (PVL) gene analysis using modifications of previously published methods (14,18,20). Details of the epidemiologic trends for the entire collection were recently published (23).…”
Section: Bacterial Isolatesmentioning
confidence: 99%